Compensatory responses of vital rates attenuate impacts of competition on population growth and promote coexistence. (27th January 2023) - Lyu, Shengman; Alexander, Jake M.
Abstract: Competition is among the most important factors regulating plant population and community dynamics, but we know little about how different vital rates respond to competition and jointly determine population growth and species coexistence. We conducted a field experiment and parameterised integral projection models to model the population growth of 14 herbaceous plant species in the absence and presence of neighbours across an elevation gradient (284 interspecific pairs). We found that suppressed individual growth and seedling establishment contributed the most to competition‐induced declines in population growth, although vital rate contributions varied greatly between species and with elevation. In contrast, size‐specific survival and flowering probability and seed production were frequently enhanced under competition. These compensatory vital rate responses were nearly ubiquitous (occurred in 92% of species pairs) and significantly reduced niche overlap and stabilised coexistence. Our study highlights the importance of demographic processes for regulating population and community dynamics, which has often been neglected by classic coexistence theories. Abstract : This study combines a field experiment with population modelling to examine how individual vital rates respond to competition and jointly determine population growth under competition and coexistence between 14 herbaceous plant species in the Swiss Alps. It found that size‐specific survival, flowering probability and seed production were frequently enhanced under competition; these widespread compensatory responses of vital rates significantly reduced niche overlap and stabilised coexistence. This study highlights the importance of demographic processes within populations for regulating community dynamics, which has often been neglected by classic coexistence theories.